Soil carbon stocks at the Subarctic mountain Birch treeline after Moth outbreaks - Xu, Yi (Helsingin yliopisto, 2020)
Tiivistelmä/Referat – Abstract Global warming and its coinstantaneous disturbance are intensively influencing the northern area. As a major natural disturbance in northern forest, winter moth (Operophtera brumata) and autumn moth (Epirrita autumnata) has caused wide defoliation in the mountain birch forest (Betula pubescens ssp. czerepanovii) at the subarctic area, exerting great impact on soil C stocks. Increasing temperature has promoted the vegetation expansion in the northern area and elevated the plant productivity, leading to higher C input to soil C stock. Litter decomposition may be accelerated by higher temperature, which decreases soil C storage. Moth herbivory usually increases the soil C stock in the short-term through litter and frass deposition, despite its aboveground suppression on photosynthesis. Belowground microbial community and composition shift would happen after moth outbreak, mediating the soil C turnover. However, the long-term effect of moth outbreak on soil C stock is still uncertain. This study investigated the influence of different tree status on soil C stock at subarctic mountain birch treeline forest, which went through severe moth outbreaks at 10 and 60 years ago. Living trees have observed with higher soil C stock than dead trees and treeless tundra, indicating the living tree may have a positive impact on soil C stock probably due to great aboveground photosynthesis. Living tree and its understory vegetation enhanced the soil respiration and ecosystem respiration, which would speed the C turnover, especially in the peak growing season. Dead trees were observed with slightly higher soil C stock than treeless tundra, both at 10 and 60 years’ perspectives. In contrast to direct C input provided by the living tree, the positive effect of dead tree on soil C stock is mainly due to the recalcitrant accumulation in the soil organic layer. Thus, soil C stock at the subarctic treeline after moth outbreak showed variations depending on the tree status, but overall remained as a C sink, ...